Culture of Digital and Audiovisual Literacy among University Students - Sánchez Márquez, Wilberto; Peña Maldonado, Alma Alicia; Cervantes López, Miriam Janet; Cruz Casados, Jaime (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
In the contemporary era, digital literacy has become an inescapable imperative, and university students are part of the generation that has grown up immersed in the digital world. The objective was to analyze the culture of digital literacy in students. A descriptive, observational and cross-sectional study was followed, the sample was 320 students, resulting in a good attitude towards technologies due to the familiarity of their use. The use of ICTs represents an invaluable support for students by facilitating research in the scientific and medical fields.